The Urgency of the Second Amendment to ITE Law from the Standpoint of the Positive Law and Human Rights - Hasyim, A. Dardiri; Darsinah, Darsinah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The ITE Law experienced modifications in 2016 with the enactment of Law No. 19 of 2016, which amends Law No. 11 of 2008 regarding ITE. In 2023, the ITE Law will see a reemergence of changes. This article seeks to delve deeper into the pressing nature of these changes through the lens of human rights. This research uses normative legal methods with a legislative approach with a human rights perspective. Data collection through literature reviews relevant to the research focus, including literature reviews, theoretical frameworks, and government regulatory documents. This article concludes that the existing findings show that the proposed amendments are already regulated in existing laws and regulations, thus indicating that there is no urgent need to revise the ITE Law. Out of the seven proposed changes, five hav been addressed in other laws and regulations. If the changes persist, there will be overlapping regulations that could undermine the positive legal framework in Indonesia. At the same time, two proposed changes regarding the consequences of criminal threats and sanctions have been incorporated into the Criminal Code, which was ratified and enacted at the end of 2022 and is set to take effect in 2026. The ITE Law, when viewed alongside regulations from other countries, has strayed from its initial purpose as a protector of electronic activities and has instead become a means of legitimizing criminalization. This clearly indicates that the ITE Law is inconsistent with human rights.